Insights from Japanese Urban Policies for Sustainable City Planning in Nepal - Shrestha, Sunil Babu (NCWA Annual Journal, 2026)
Nepal is a landlocked country with a rapidly increasing urban population. It is experiencing crucial challenges in creating sustainable cities. Urban municipalities now account for over 66% of the nation’s population. There is a growing demand for adequate infrastructure, affordable housing, and effective disaster management to cater to the needs of the increasing population. Based on the review of the secondary data, this article discusses the most critical urban issues in Nepal, which include climate change impacts, informal settlements and infrastructure deficiency. It highlights the need for integrated urban planning and policy action to make cities more livable and resilient. Nepal can develop approaches to address its urban issues by assembling lessons from Japan’s city policies and practices, such as comprehensive land-use planning, community participation, and disaster resilience. Nepal can take advantage of Japan’s experience in promoting green spaces and low-cost housing, urban agriculture as the route to climate resilience, inclusive growth, and environmental sustainability. The article advocates making intergovernmental coordination better and emphasizes the collaborative efforts with the private sector to develop creative methods in dealing with urban problems. And finally, through these lessons, Nepal can navigate the way towards sustainable, climate-resilient urbanization, improving the quality of life of the people and achieving its long-term sustainable development objectives.